The Role of Language Proficiency in Academic Success for International Students: A Case Study Approach - Mohamed Ali Hamade; Noor Azizi Ismail; Siti Nurul Asyiqin Mohamed (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the role of language proficiency in determining academic success among international students. Using a case study approach, the study focuses on international students across several disciplines to assess the impact of language skills on academic performance, participation, and peer integration. Results demonstrate that language proficiency significantly correlates with academic outcomes and engagement levels, emphasizing the need for universities to provide targeted language support services.